Construction of a reading literacy test item bank for fourth graders based on item response theory - Chen, Qishan; Zheng, Haiyan; Fan, Honglan; Mo, Lei (Frontiers in Psychology, 2023)
Reading literacy is not only central to students’ academic success during their school years but also crucial to their personal development in their later life. The development of assessment instruments for reading literacy has been of interest to researchers, educators and educational administrators. The purpose of the present study was to construct and validate a comparable item bank for assessing fourth-grade students’ reading literacy. One hundred fifteen reading comprehension items were developed and administered to 2174 Grade 4 students to construct an item bank. Using the test equating technique and balanced incomplete block design, we divided participants into ten subgroups, and the one hundred and fifteen items were further assigned into ten test forms. Item response theory software was used to estimate discrimination, threshold parameters of items, and students’ ability parameters. The criterion-related validity was also examined in 135 Grade 4 students who completed the reading literacy test and verbal self-description questionnaire. The final item bank included 99 reading performance indicators to express high achievement. The correlation between the student’s reading literacy and the verbal self-description questionnaire was significant and demonstrated the item bank’s good criterion-related validity. The item bank developed in this study shows good psychometric characteristics and can be used to assess the reading literacy of fourth graders.